Infecções helmínticas em Sus scrofa scrofa (javali) de criatório comercial no sul do Brasil - Silva, Diego Silva da (2012)
The meat of the wild boar has always been regarded noble, possessing a distinctive flavor, and has low fat and cholesterol. These characteristics give the meat a great potential gastronomic, so the commercial breeding boars may be considered a promising market. This study aimed to identify the species of helminths that inhabit the digestive and respiratory tract of Sus scrofa scrofa from commercial breeding. Were collected and individually the digestive and respiratory tracts of 40 wild boars from commercial breeding during the slaughter process in the slaughterhouse. Of the 40 animals analyzed, 87.5% were parasitized by helminths, they being, with their respective prevalence, Trichuris suis (67,5%), Ascaris suum (47,5%), Trichostrongylus colubriformes (45%), which has first recorded parasitizing wild boars, and Oesophagostomum dentatum (5.0%). With respect to the parasites of the respiratory tract, the genus Metastrongylus was recorded in the bronchi and bronchioles in 60% of animals tested, with the occurrence of three species with their respective prevalence, M. apri (52,5%), M. salmi (20%) and M. pudendotectus (7,5%), registering the highest prevalence of Metastrongylus in wild boars from commercial breeding of so far. With the exception of O. dentatum, the other parasites have their first record parasitizing wild boar in a subtropical region.